1948
DOI: 10.2113/gssgfbull.s5-xviii.1-3.167
|View full text |Cite
|
Sign up to set email alerts
|

Le regime hydro-geologique des calcaires eocenes du synclinal du Dyr el Kef (Tunisie)

Abstract: Measurements of the flow of the Kef spring, the only point of emergence of water from Eocene limestones of the Dyr el Kef synclinal basin, Tunisia, together with data on precipitation, show that two hydraulic systems operate within the limestone aquifer. The limestones are exposed over a considerable area, and because of the almost complete absence of vegetation, the intake coefficient is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…The first studies that tried to decompose the recession hydrograph, considering the participation of various flow components during the recession process, were already started by Maillet (1905). Here, and also in later studies by Barnes (1939), Schöeller (1948), Werner and Sundquist (1951), Forkasiewicz and Paloc (1967), Hall (1968), Drogue (1972), Kullman (1980), Milanovic (1981), and Padilla et al (1994), only two basic flow components were recognized. Later studies (e.g.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The first studies that tried to decompose the recession hydrograph, considering the participation of various flow components during the recession process, were already started by Maillet (1905). Here, and also in later studies by Barnes (1939), Schöeller (1948), Werner and Sundquist (1951), Forkasiewicz and Paloc (1967), Hall (1968), Drogue (1972), Kullman (1980), Milanovic (1981), and Padilla et al (1994), only two basic flow components were recognized. Later studies (e.g.…”
Section: Introductionsupporting
confidence: 74%
“…Baseflow separation still features in the most recent studies in catchment hydrology by Salas Aguilar et al (2017), Jakada et al (2019) and Soto (2019). Schöeller (1948Schöeller ( , 1965, followed by Forkasiewicz and Paloc (1967) and Drogue (1972), was probably the first to apply recession curve analysis targeted directly at karst water hydrographs. The first studies that tried to decompose the recession hydrograph, considering the participation of various flow components during the recession process, were already started by Maillet (1905).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the overall shapes of any recession curve are similar, differences are observed from one to another (Dewandel et al 2003). The shape of the curve can change with the aquifer properties (Schoeller 1948;Forkasiewicz & Paloc 1967;Drogue 1967), and geometry of the aquifer system (Horton 1945;Eisenlohr et al 1997).…”
Section: Recession Analysismentioning
confidence: 99%
“…If the semi-log plotted recession curve shows one linear trend, it can be mathematically explained using one exponential equation. If more than one linear trend, each trend should be explained using separate exponential equations, and the sum of these equations gives the total flow equation, which is called "Modified Maillet Formula" (Barnes 1939;Schoeller 1948;Forkasiewicz & Paloc 1967;Fu et al 2016). In this study, we determined the recession coefficients using Maillet exponential equation, and we defined recession equations by using a modified Maillet formula.…”
Section: Recession Analysismentioning
confidence: 99%
“…In Tunisia, Tixeront et al [14] measured that 16% to 49% of annual precipitation recharged a Senonian monocline and two Jurassic limestone horsts over four years. Schoeller found that the recharge rate of a 5.8 km 2 Tunisian Eocene limestone syncline groundwater basin to Kef Spring varied annually over eight years from 30% to 90% depending on the amount of precipitation, intensity of rainfall and groundwater-level conditions [15]. Over 19 km 2 of the Djebel Bargou Aptial limestone syncline of Tunisia, Zebidi [16] measured 18% recharge rate over two years.…”
Section: Introductionmentioning
confidence: 99%